NON-LINEAR 3D TOMOGRAPHIC STUDY FOR GUNTUR VOLCANO USING P AND S ARRIVAL TIME DATA : Abstract - Dian Nugraha NIM. 224 03 001, Andri
Abstract: In this study, P and S arrival times have been used to investigate the internal structure of the Guntur volcano. In the process of hypocenter determination we employed a grid search method using a 1D velocity layer. A three circles intersection method has been used to guide the grid search method. In the tomographic process, the minimum traveltime from a source to a receiver has been calculated by employing 3D ray tracing with a pseudo bending method. Based on an irregular source and receiver distribution the block element has been chosen to be 2 x 2 x 2 km3. Input data for tomographic inversion are delay time (δt) defined as the difference between the travel time of seismic wave in the Earth (tobs) and in the reference velocity model (tcal). In this investigation the main problem of tomographic inversion with a linear approach is to obtain the solution of linear equation using the LSQR method. We applied explicit damping that consists of minimum norm and gradient damping. The P and S wave tomograms indicate that there are several negative anomalies under the Guntur volcano associated with hot materials beneath the Kamojang caldera, Gandapura caldera, and Guntur summit. Negative anomalies in the P and S wave models relate to a positive anomaly in the PoissonÂ’s ratio tomogram. This relation suggests that the associated volcano material tends to be more fluidlike. Meanwhile, the negative anomalies in the P and S wave models associate with a positive anomaly in the bulk sound velocity tomogram. This may be interpreted that the material tends to be more incompressible.